Relationship of biomarkers of extracellular matrix with myocardial function in Type 2 diabetes mellitus. (July 2017) - Liu, Ju-Hua; Chen, Yan; Zhen, Zhe; Ho, Lai-Ming; Tsang, Anita; Yuen, Michele; Lam, Karen; Tse, Hung-Fat; Yiu, Kai-Hang
Aim: The study evaluated the relationship of extracellular matrix and renin angiotensin system with myocardial dysfunction in Type 2 diabetes mellitus.Methods: All patients underwent resting and exercise echocardiography, including conventional parameters, E/E′ ratio, global longitudinal strain and diastolic function reserve index. Plasma matrix metalloproteinase-1, TIMP-1, amino-terminal propeptide of type I and type III procollagen and renin angiotensin system activity were measured.Results: As patients with diastolic dysfunction had a higher plasma level of TIMP-1 and propeptide of type III procollagen than those with no diastolic dysfunction. After multivariate adjustment, TIMP-1 associated with E/E′ (both at rest and stress) and diastolic function reserve index.Conclusion: TIMP-1 is independently associated with myocardial diastolic dysfunction in patients with Type 2 diabetes mellitus.